Treatment of facial erythema in patients with rosacea with topical brimonidine tartrate: correlation of patient satisfaction with standard clinical endpoints of improvement of facial erythema. (30th July 2014) - Fowler, J.; Tan, J.; Jackson, J.M.; Meadows, K.; Jones, T.; Jarratt, M.; Leoni, M.; the Brimonidine Phase III Study Group
Abstract Background Once‐daily brimonidine tartrate (BT) 0.5% gel was shown to provide significantly greater efficacy vs. vehicle for the treatment of facial erythema in patients with rosacea. Objectives To demonstrate that patient satisfaction with overall appearance is correlated with reduction in facial erythema, as measured by clinician and patient assessments. Methods Data from two identical phase III, multicentre, randomized, controlled trials of moderate facial erythema of rosacea (study A: n = 260; study B: n = 293) with topical BT 0.5% compared to vehicle gel once‐daily for 4 weeks were analysed. Correlations of Patient's Assessment of Appearance (PAA) with Clinician's Erythema Assessment (CEA) and Patient's Self‐Assessment (PSA) of erythema were evaluated by calculation of gamma statistics. Results PAA correlated with CEA post‐application on Days 1, 15 and 29 for the intent‐to‐treat population and provided a median gamma value of 0.57 (min = 0.28, max = 0.61). PAA and PSA was also highly correlated post‐application on Days 1, 15 and 29; with a median gamma value of 0.87 (min = 0.66, max = 0.89). Subjects who achieved a clinically meaningful improvement in both CEA and PSA scales were more likely to report satisfaction with the overall appearance of their skin (P < 0.001). Conclusions Both one‐ and two‐grade improvements in facial erythema assessed by subjects (PSA) and clinicians (CEA) correlate well with PAA, a patient‐centered representation of meaningful change.